Delayed graft function and its impact on short- and long-term outcomes after kidney transplantation - Kilic, Jehat; Esen, Rengin; Varhan, Caner; Alakus, Omer Faruk; Kilic, Delyadil Karakas; Danis, Ramazan (Bmc, 2026)
Introduction Kidney transplantation is an effective treatment for end-stage renal disease, markedly improving survival and quality of life. However, delayed graft function (DGF) remains a notable early post-transplant complication. This study examine the impact of DGF on mortality, hypertension, graft survival, and other post-transplant complications. Methods This retrospective study included adult recipients (>= 18 years) who underwent kidney transplantation at the Organ Transplant Unit of Diyarbak & imath;r Gazi Ya & scedil;argil Training and Research Hospital between 1 January 2013 and 31 December 2023. A total of 285 patients with at least 12 months of follow-up were analyzed. Demographic characteristics, presence of post-transplant hypertension, immunosuppressive regimens, and laboratory parameters related to graft function were extracted from the Hospital Information Management System (HIMS) using a standardized abstraction form. Post-transplant hypertension was defined according to the KDIGO 2021 guideline; details of the analytic approach are described in the Statistics section. Results A total of 285 kidney transplant recipients were included, with DGF observed in 31 patients (10.9%). Baseline characteristics such as recipient age, sex, BMI, and pre-transplant hypertension were comparable between groups (p > 0.05). Patients with DGF had significantly older donors (p = 0.006), a higher proportion of non-related donors (p = 0.001), longer dialysis duration (p = 0.008), and more frequent deceased donor transplantation (35.5% vs. 5.9%, p < 0.001). Postoperative complications and mortality were also higher in the DGF group (p = 0.003 and p < 0.001, respectively). In univariate analysis, non-related donor status, postoperative events, discharge protein levels, and dialysis duration were associated with DGF. In multivariate analysis, deceased donor status (OR = 4.883, p = 0.015), postoperative events (OR = 3.336, p = 0.011), and discharge protein levels (OR = 1.007, p = 0.033) remained independent predictors. Conclusion DGF was associated with adverse outcomes after kidney transplantation. Deceased donor status, postoperative events, and higher discharge protein levels were identified as independent predictors, underscoring the multifactorial nature of DGF. Early identification of high-risk patients and close post-transplant monitoring may improve clinical outcomes.
Keywords: Kidney Transplantation; Post-Transplant Hypertension; Delayed Graft Function; Graft Dysfunction; Immunosuppression